Data inputs and assumptions in calculating the non-fatal burden in burden of disease studies. (30th September 2020) - Haagsma, J; Wyper, G; Devleesschauwer, B
Abstract: Years Lived with Disability (YLD) is a component of the Disability-Adjusted Life Year (DALY), and measures the healthy time that is lost because of living with a disease or disability. YLDs are calculated by multiplying the prevalence and/or incidence of a disorder by the short- or long-term loss of health associated with that disability (the disability weight) and disease severity (severity distribution). The process of calculating a YLD involves several components and in this presentation each step will be highlighted through a sequential walk through for each step in the YLD calculation, including counting disease occurrence the relationship between disability weights, health states and severity distributions adjusting for comorbidities dealing with uncertainty The aim of this presentation is to provide a simple step by step guide on the key components in the YLD calculation. Using the real-life example of cerebrovascular disease, the presentation will outline the key choices and assumptions that underline each data input in the YLD calculation. Participants in this session will also be provided with links to resources to help facilitate this decision-making process. The workshop will end with an interactive session where the presenters will discuss the implications of the different methodological choices with the audience.